Nonwoven fabric for absorbent article and manufacturing method thereof

By using nonwoven fabrics composed of composite fibers and recycled fibers with high polyester resin content, and forming penetration holes during the water flow textile process, the shortcomings of the existing absorbent nonwoven fabrics in liquid absorption performance and liquid prevention reflux are solved, and the liquid absorption performance is improved and the liquid reflux prevention is prevented.

JP2025063386APending Publication Date: 2025-04-16SHINWA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172511
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

The existing absorbent nonwovens have shortcomings in liquid absorption performance and liquid retardant return, especially the liquid absorption performance is poor and the liquid is prone to reflux to the skin, resulting in discomfort in wear.

Method used

A nonwoven fabric composed of composite fibers and recycled fibers with high polyester resin content is used to superimpose the first mesh of the high-content composite fiber and the second mesh of the high-content recycled fibers, and a large number of penetration holes are formed during the water flow textile process to enhance the liquid absorption performance and prevent liquid reflux.

Benefits of technology

The improvement of liquid absorption performance and effective prevention of liquid reflux are achieved, and an absorption nonwoven fabric that can quickly absorb liquid and prevent liquid reflux after multiple liquid absorption is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063386000001_ABST
    Figure 2025063386000001_ABST
Patent Text Reader

Abstract

To obtain a nonwoven fabric for absorbent article having further improved performance so as to provide an absorbent article capable of quickly absorbing liquid and hardly causing the liquid to return to skin even if repeatedly absorbing the liquid.SOLUTION: A nonwoven fabric for absorbent article is a nonwoven fabric consisting of composite fibers including polyolefin-based resin and regenerated cellulose fibers. The nonwoven fabric is formed by overlapping a first web containing 90 mass% or more of the composite fibers and a second web containing 25 mass% or more of the regenerated cellulose fibers and entangling the webs by water flow and has many open holes penetrating in a thickness direction of the nonwoven fabric.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonwoven fabric for absorbent articles used in absorbent articles such as disposable diapers, and a method for producing the nonwoven fabric for absorbent articles. [Background technology]

[0002] In general, absorbent articles have a sheet-like absorbent body containing a highly water-absorbent polymer for absorbing liquids such as urine, and this absorbent body is sandwiched between a liquid-permeable top sheet arranged on the skin side of the absorbent article and a liquid-impermeable back sheet arranged on the opposite side to the skin side. The nonwoven fabric for absorbent articles of the present invention is used by being arranged on the skin side of the absorbent body as a top sheet, and is required to quickly transfer liquid adhering to its skin-side surface to the absorbent body and absorb it, and to prevent the liquid absorbed by the absorbent body from returning to the skin, so as to minimize discomfort to the user of the absorbent article.

[0003] Conventionally, nonwoven fabrics for absorbent articles include those made of cotton-containing nonwoven fabrics composed of a surface layer and a nonwoven fabric reinforcing layer, as described in Patent Document 1. In this nonwoven fabric, the surface layer has a basis weight of 5 to 30 g / m 2 The nonwoven fabric reinforcing layer is made of a melt-blown nonwoven fabric, a spunbonded nonwoven fabric, or a hot-rolled nonwoven fabric. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2016-529412 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the above-mentioned nonwoven fabric for absorbent articles, the nonwoven fabric reinforcing layer increases the strength of the nonwoven fabric for absorbent articles, but has inferior water absorption properties compared to cotton fibers, thereby reducing the ability of the nonwoven fabric for absorbent articles to quickly transfer liquid to the absorbent body and absorb it.

[0006] In addition, since cotton fibers are used in the surface layer that faces the skin, the fabric feels soft to the touch, but if the cotton fibers are hydrophilic, they tend to retain liquid in the surface layer, which then returns to the skin from the surface layer, making the fabric sticky and causing discomfort to the wearer of the absorbent article. If the cotton fibers are hydrophobic, the raw cotton fibers are inherently hydrophilic, so in order to obtain hydrophobic cotton fibers, it is necessary to subject the raw cotton fibers to a hydrophobic treatment, such as by adding a hydrophobic treating agent, which not only increases the manufacturing cost of the nonwoven fabric for absorbent articles, but also reduces the effect of the hydrophobic treatment of the hydrophobic treated cotton fibers each time they are exposed to liquids such as urine.

[0007] The present invention has been made in consideration of the above-mentioned problems in the conventional art. The object of the present invention is to provide a nonwoven fabric for absorbent articles with improved performance so as to provide an absorbent article that quickly absorbs liquid and does not easily return liquid to the skin even after repeated liquid absorption. Means for solving the problem and effects of the invention

[0008] The nonwoven fabric for absorbent articles according to the first aspect of the present invention is a nonwoven fabric consisting of composite fibers containing a polyolefin resin and regenerated cellulose fibers, and is formed by overlapping and hydroentangling a first web containing 90% or more by mass of the composite fibers and a second web containing 25% or more by mass of the regenerated cellulose fibers, and can be configured to have a large number of through holes that penetrate the thickness direction of the nonwoven fabric.

[0009] With the above-mentioned configuration, the nonwoven fabric for absorbent articles has improved performance and contains hydrophilic regenerated cellulose fibers having through holes at a certain content range, and the regenerated cellulose fibers are also entangled with the composite fibers contained in the first web, so that liquid on the skin side can be quickly transferred to the absorbent body and absorbed, and the first web contains a high content of composite fibers containing a polyolefin resin whose water repellency does not decrease even when it comes into contact with liquid, and the second web also contains the composite fibers at a certain content range, so that even if the absorbent body repeatedly absorbs liquid, the liquid can be prevented from returning to the skin from the absorbent body. Thus, a nonwoven fabric for absorbent articles with improved performance can be obtained, so that an absorbent article can be provided that quickly absorbs liquid and does not easily return liquid to the skin even if it is repeatedly absorbed.

[0010] According to the nonwoven fabric for absorbent articles according to the second aspect of the present invention, the second web can be configured to contain 25 to 80 mass % of regenerated cellulose fibers and 20 to 75 mass % of the composite fibers.

[0011] This configuration makes it possible to improve in a balanced manner the performance of the nonwoven fabric for absorbent articles in quickly transferring liquid adhering to the skin-facing surface to the absorbent body and absorbing it, and in preventing liquid absorbed by the absorbent body from returning to the skin-facing surface.

[0012] According to the nonwoven fabric for absorbent articles relating to the third aspect of the present invention, the composite fibers can be configured as eccentric core-sheath type composite fibers in which the sheath portion is made of polyethylene resin.

[0013] With this structure, the composite fibers are coiled, so that the nonwoven fabric has a large space between the fibers and is bulky, making it difficult for absorbed liquid to return from the absorbent body to the skin.

[0014] The nonwoven fabric for absorbent articles relating to the fourth aspect of the present invention can be configured so that the sheath portions of the eccentric core-sheath type composite fibers are not fused to each other, the sheath portions are not fused to the regenerated cellulose fibers, and the regenerated cellulose fibers are not fused to each other.

[0015] With this configuration, it is possible to obtain a product that has a relatively soft texture and is pleasant to the touch.

[0016] According to the nonwoven fabric for absorbent articles relating to the fifth aspect of the present invention, the composite fibers and the regenerated cellulose fibers are each short fibers, and at least the composite fibers in the first web and the regenerated cellulose fibers in the second web can be configured to be entangled.

[0017] With the above-mentioned structure, it is easy to obtain the first web and the second web having the required content of bicomponent fiber and regenerated cellulose fiber and the required mechanical strength.

[0018] A method for producing a nonwoven fabric for absorbent articles according to a sixth aspect of the present invention includes: loosening raw cotton of composite fiber containing a polyolefin resin to form a first raw fiber; or loosening the raw cotton of the composite fiber and the raw cotton of regenerated cellulose separately, mixing the loosened composite fiber and the regenerated cellulose fiber so that the composite fiber accounts for 90% by mass or more to form a first raw fiber; and combing the first raw fiber with a carding machine to form a first web; and loosening the raw cotton of the regenerated cellulose fiber and the raw cotton of the composite fiber containing a polyolefin resin separately, mixing the loosened regenerated cellulose fiber and the composite fiber so that the regenerated cellulose fiber accounts for 25% by mass or more to form a second raw fiber. the second raw fiber is carded with a carding machine to form a second web; a lamination process in which the first web and the second web are overlapped to obtain a laminated web; a hydroentanglement process in which the laminated web is supported by a mesh-like support arranged on the second web side of the laminated web and travels together with the support while spraying high-pressure water from a number of nozzles arranged on the first web side toward the laminated web, thereby hydroentanglement of the first raw fiber and the second raw fiber and obtaining a wet nonwoven fabric having a number of through holes; and a drying process in which the wet nonwoven fabric obtained in the hydroentanglement process is heated and dried.

[0019] With the above-mentioned configuration, it is possible to obtain a nonwoven fabric for absorbent articles with improved performance, so as to provide an absorbent article that quickly absorbs liquid and is less likely to return liquid to the skin even after repeated liquid absorption. [Brief description of the drawings]

[0020] [Figure 1] 1 is a photograph showing a plan view of a nonwoven fabric for absorbent articles according to one embodiment of the present invention. [Diagram 2] 2 is an enlarged photograph of a cut section of the nonwoven fabric for absorbent articles shown in FIG. 1. [Diagram 3] FIG. 2 is a graph showing the relationship between the rayon content and the liquid absorption time and the amount of liquid wetback. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, embodiments of the present invention will be described. However, the embodiments shown below are merely examples of a nonwoven fabric for absorbent articles and a method for producing the same to embody the technical concept of the present invention, and the present invention is not limited to the following.

[0022] The nonwoven fabric for absorbent articles according to one embodiment of the present invention is used as a top sheet by overlapping the surface side of an absorbent body of an absorbent article, that is, the skin side of a person wearing the absorbent article, and is a nonwoven fabric made of composite fibers containing polyolefin resin and regenerated cellulose fibers, and is formed by overlapping and hydroentangling a first web containing 90% by mass or more of the composite fibers and a second web containing 25% by mass or more of the regenerated cellulose fibers. As shown in FIG. 1, this nonwoven fabric has a large number of through holes penetrating the nonwoven fabric in the thickness direction. The nonwoven fabric for absorbent articles of the present invention can also be used as a second sheet inserted between the top sheet and the absorbent body.

[0023] The first web overlaps the skin side of the second web, and the surface of the first web faces the skin of a person wearing the absorbent article. Fig. 2 shows a cut surface of this nonwoven fabric in the thickness direction, with the upper side being the skin side and the lower side being the absorbent body side in Fig. 2. In this nonwoven fabric, the fibers constituting the first web and the fibers constituting the second web are entangled, and even when the cut surface is visually observed, the boundary between the first web and the second web is unclear and cannot be identified, as shown in Fig. 2.

[0024] In order to further improve the performance of this nonwoven fabric for absorbent articles in quickly transferring and absorbing liquid into the absorbent body, and in preventing liquid absorbed by the absorbent body from returning to the skin, it is desirable for the second web to contain 25 to 80 mass % of regenerated cellulose fibers and 20 to 75 mass % of the composite fibers.

[0025] Furthermore, in order to form the nonwoven fabric for absorbent articles into a bulky one with large spaces between the fibers so that absorbed liquid is less likely to return to the skin from the absorbent body, it is preferable that the composite fibers be eccentric core-sheath type composite fibers in which the sheath portion is made of polyethylene resin.

[0026] Furthermore, in order to make the nonwoven fabric for absorbent articles even softer and more pleasant to the touch, it is desirable that the sheath portions of the eccentric core-sheath type composite fibers, the sheath portions and the regenerated cellulose fibers, and the regenerated cellulose fibers themselves are not fused to each other.

[0027] Furthermore, in order to obtain a nonwoven fabric for absorbent articles in which the first web and the second web have the required composite fiber content and regenerated cellulose fiber content, and which has the required mechanical strength, it is desirable that the composite fibers and the regenerated cellulose fibers are each short fibers, and that at least the composite fibers in the first web and the regenerated cellulose fibers in the second web are entangled.

[0028] Next, a method for producing a nonwoven fabric for absorbent articles according to one embodiment of the present invention will be described. The method for producing a nonwoven fabric for absorbent articles includes a web forming step, a lamination step, a hydroentanglement step, and a drying step. (Web forming process)

[0029] In the web forming step, raw cotton of composite fiber containing polyolefin resin is loosened to form first raw fiber, and the first raw fiber is carded to form a first web, and raw cotton of regenerated cellulose fiber and raw cotton of composite fiber containing polyolefin resin are loosened respectively to mix the regenerated cellulose fiber and the composite fiber so that the regenerated cellulose fiber is 25% by mass or more to form a second raw fiber, and the second raw fiber is carded to form a second web. Note that, instead of loosening raw cotton of composite fiber containing polyolefin resin to form the first raw fiber, raw cotton of composite fiber and raw cotton of regenerated cellulose may be loosened respectively, and the loosened composite fiber and the regenerated cellulose fiber may be mixed to mix the composite fiber so that the composite fiber is 90% by mass or more to form the first raw fiber.

[0030] The raw cotton of the composite fiber and the regenerated cellulose fiber before being loosened is each composed of many short fibers and compressed. The second raw fiber is a mixture of the short fibers of the regenerated cellulose fiber and the short fibers of the composite fiber, each of which is uniformly distributed in a predetermined amount within the second raw fiber. The carding machine is a known machine that scrapes and loosens the raw fiber by passing it over many rollers, and the raw fiber that has passed through the carding machine becomes a web with the fiber direction aligned. (Lamination process)

[0031] In the lamination step, the first web and the second web are laminated together to obtain a laminated web. (Hydroentanglement process)

[0032] In the hydroentanglement process, the laminate web is supported by a mesh-like support arranged on the second web side of the laminate web and moved together with the support, while high-pressure water is sprayed toward the laminate web from a number of nozzles arranged on the first web side, thereby hydroentanglement of the first raw fiber and the second raw fiber and obtaining a wet nonwoven fabric having a number of through holes.

[0033] When the first raw fiber and the second raw fiber are hydroentangled to form through holes, high-pressure water is sprayed from the first web toward the laminated web, which prevents the hydrophilic regenerated cellulose fiber in the second web from penetrating the hydrophobic composite fiber in the first web and appearing in large quantities on the skin-side surface of the nonwoven fabric, thereby making it difficult for the liquid absorbed by the absorbent to return to the skin. In addition, the net-like support has a support portion that can support the laminated web from below and a hole portion that cannot support the laminated web, and the high-pressure water sprayed toward the laminated web penetrates the hole portion of the support. As a result, the through holes are formed in the wet nonwoven fabric. At that time, the fibers in the hole portion of the support of the laminated web are pushed downward from the hole portion of the support by the high-pressure water, and the fibers in the pushed-out portion are peeled off from the center of the pushed-out portion to the periphery of the support and rolled up downward, so that the wet nonwoven fabric is prone to have downward bulges around the through holes. These raised portions remain as protruding portions even after the wet nonwoven fabric dries, and are considered to function to increase the distance from the absorbent body to the skin-facing surface of the absorbent article when the nonwoven fabric for absorbent articles is overlapped with an absorbent body, making it difficult for liquid absorbed by the absorbent body to return to the skin. The size and distribution of the through holes are related to the ease with which liquid can move to the absorbent body and the difficulty with which liquid can return from the absorbent body to the skin, and it is desirable for the diameter of the through holes to be approximately 0.5 mm to 2.5 mm.

[0034] In the hydroentanglement process, the laminated web is supported by a support having fine pores with a mesh size of about 60 to 150 mesh, and while the support and the web are running together, high-pressure water is sprayed onto the laminated web to entangle the first raw fiber and the second raw fiber. After that, the laminated web is supported by a support having large pores with a mesh size of about 6 to 20 mesh, and while the support and the web are running together, high-pressure water is sprayed onto the laminated web from a number of nozzles arranged on the first web side, whereby the first raw fiber and the second raw fiber are further hydroentangled and a number of through holes are formed. (drying process)

[0035] In the drying step, the wet nonwoven fabric obtained in the hydroentanglement step is heated and dried. This results in the nonwoven fabric for absorbent articles. To heat and dry the wet nonwoven fabric, the wet nonwoven fabric is introduced into, for example, a drying oven and hot air is blown onto it. At this time, in order to dry the wet nonwoven fabric without fusing the sheaths of the eccentric core-sheath type composite fibers to each other, the sheaths to the regenerated cellulose fibers, and the regenerated cellulose fibers to each other, it is preferable to adjust the temperature of the hot air to within a range of 80°C to 125°C. EXAMPLES

[0036] The present invention will be described in more detail below with reference to examples. Table 1 below shows a summary of various examples and comparative examples obtained by carrying out the manufacturing method of a nonwoven fabric for absorbent articles according to one embodiment of the present invention, in order to evaluate the performance of quickly transferring discharged liquid to the absorbent body and absorbing it, and the performance of preventing the liquid absorbed by the absorbent body from returning to the skin.

[0037] [Table 1]

[0038] In Table 1, the liquid absorption time is an index of the ability to quickly transfer liquid administered to the skin-facing surface to the absorbent body and absorb it, while the liquid return amount is an index of the ability to prevent liquid absorbed by the absorbent body from returning to the skin-facing surface. The methods for calculating the basis weight, thickness, liquid absorption time, and liquid return amount are as follows. (Met)

[0039] The basis weight was measured based on JIS L 1913:1998 6.2. Specifically, three test pieces measuring 200 mm x 200 mm were taken from the nonwoven fabric to be evaluated. The mass of each test piece (three pieces) was measured under standard conditions and divided by the area to obtain the basis weight (g / m 2 ) and the average value was calculated. (Thickness)

[0040] The thickness was measured based on JIS L1913:1998 6.1.2 Method A. Specifically, five test pieces measuring 50 mm x 50 mm were taken from the nonwoven fabric to be evaluated. The thickness (mm) was measured by applying a pressure of 0.34 kPa to the test pieces under standard conditions using a thickness measuring device (Peacock thickness meter manufactured by Daiei Scientific Instruments, terminal: φ44 mm). Measurements were performed on each test piece (five pieces) and the average value was calculated. (Liquid absorption time)

[0041] The liquid absorption time was calculated as follows. First, three test pieces of 180 mm x 180 mm were taken from the nonwoven fabric to be evaluated. On the other hand, a 0.9% by mass aqueous solution of sodium chloride was prepared as artificial urine. Then, 20 g of a mixture of superabsorbent polymer and pulp was weighed out and spread on a polyethylene film to a size of 180 mm x 180 mm, the test piece was placed on top of this so that the first web was on the upper surface, and a stainless steel pressing plate (210 mm x 297 mm, 4.6 kg) was placed and pressed. After removing the pressing plate, 150 g of the artificial urine was administered from a height of 3 cm to the center of the test piece. At this time, the artificial urine was administered as quickly as possible so that it did not leak sideways from the upper surface of the test piece. The time from the start of administration until the artificial urine was no longer observed on the test piece was measured, and this time was taken as the first liquid absorption time (seconds). Measurements were performed on each test piece (3 pieces) and the average value was calculated. (amount of liquid returned)

[0042] The amount of liquid return was measured as follows. First, a circular qualitative filter paper "O.1 φ110mm" manufactured by Advantec Toyo Co., Ltd. was prepared. Five sheets of filter paper were taken out and the filter paper mass (W0) before the test was measured. In the measurement of the liquid absorption time, five minutes after the artificial urine was no longer observed on the test piece, five sheets of filter paper were placed on the center of the test piece (the part where the artificial urine was administered) and a stainless steel weight (100mm x 100mm, 500g) was placed on the filter paper. Three minutes after the weight was placed, the weight was removed and the filter paper mass after the test (W1) was measured. Using the filter paper mass after the test (W1) and the filter paper mass before the test (W0), the first liquid return amount (g) was calculated by the formula (first liquid return amount = W1-W0). Measurements were performed on each test piece (three sheets) and the average value was calculated. (Repeated test of absorption time and amount of liquid return)

[0043] The repetitive test of the liquid absorption time and the amount of liquid return was carried out as follows. However, the work of spreading the mixture of superabsorbent polymer and pulp on the polyethylene film for calculating the liquid absorption time was carried out only once, and the mixture of superabsorbent polymer and pulp prepared in the first work was used thereafter. In this test, the second artificial urine was added 30 minutes after the administration of the artificial urine for the liquid absorption time, and the second liquid absorption time and the second liquid return were measured in the same manner as the calculation of the first liquid absorption time and the calculation of the first liquid return, and the third liquid absorption time, the third liquid return amount, and the fourth liquid absorption time and the fourth liquid return amount were measured in the same manner. Example 1

[0044] In Example 1, eccentric core-sheath type composite fibers (fineness 3.3 dtex, fiber length 51 mm) with a core made of polyethylene terephthalate (PET) resin and a sheath made of polyethylene (PE) resin were unraveled to prepare the first raw fiber, which was then carded to align the fiber direction and to obtain a fiber weight of 20 g / m. 2 The first web was formed in such a manner that the first web was 100% by mass of the eccentric core-sheath type composite fiber and 25% by mass of rayon (fineness 1.7 dtex, fiber length 40 mm) as regenerated cellulose fiber. The fibers were then aligned in the same direction using a carding machine to obtain a second raw fiber. 2 The second web was formed in such a manner that the first web was 100% polyester. The first web and the second web were then laminated to obtain a laminated web. This laminated web was placed on a support made of a stainless steel wire mesh (mesh size: 14 mesh) with the first web facing up, and high-pressure water was sprayed from the first web side at a pressure of 6.0 MPa to form through holes in the web to obtain a nonwoven fabric. The nonwoven fabric was dried by heating with hot air at 110°C for 5 minutes to obtain a basis weight of 40.8 g / m. 2 , thickness 1.04mm, density 0.039g / cm 3 A nonwoven fabric of

[0045] The eccentric core-sheath composite fiber has a sheath diameter of about 19 μm, a core diameter of about 13 μm, and an eccentricity of about 2 μm. The high-pressure water is sprayed from two nozzles arranged at intervals of 300 mm in the transport direction of the laminated web, and the nozzles have a large number of nozzles, each with a diameter of 0.1 mm, arranged at a pitch of 0.6 mm in the width direction of the laminated web. The wire mesh constituting the support is a plain-woven wire mesh, and the outer diameter of each of the vertical and horizontal wires constituting it is 0.5 mm, and the vertical and horizontal pitches are 1.18 mm. The through-holes formed have a diameter of about 1.0 mm in the MD direction (flow direction of the manufacturing process) and a diameter of about 0.7 mm in the CD direction (direction perpendicular to the flow of the manufacturing process). Example 2

[0046] In Example 2, 70% by mass of the eccentric core-sheath type composite fiber and 30% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web. 2 , thickness 1.05m, density 0.038 / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Example 3

[0047] In Example 3, 60% by mass of the eccentric core-sheath type composite fiber and 40% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, and the basis weight was 41.6 g / m 2 , thickness 1.00mm, density 0.042g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Example 4

[0048] In Example 4, 50% by mass of the eccentric core-sheath type composite fiber and 50% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, and the basis weight was 41.2 g / m 2 , thickness 1.06mm, density 0.039g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Example 5

[0049] In Example 5, 40% by mass of the eccentric core-sheath type composite fiber and 60% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, and the basis weight was 40.7 g / m 2 , thickness 1.01mm, density 0.040g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Example 6

[0050] In Example 6, 30% by mass of the eccentric core-sheath type composite fiber and 70% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, and the basis weight was 39.8 g / m 2 , thickness 0.96mm, density 0.041g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Example 7

[0051] In Example 7, the eccentric core-sheath type composite fiber was not used to obtain the second raw fiber for forming the second web, and 100% by mass of rayon was used as the regenerated cellulose fiber. 2 , thickness 0.93mm, density 0.044g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Comparative Example 1

[0052] In Comparative Example 1, 50% by mass of the eccentric core-sheath type composite fiber and 50% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, a wire mesh having a mesh size of 80 mesh was used as a support in the hydroentanglement step, and the basis weight was 41.6 g / m 2 , thickness 0.92mm, density 0.045g / cm 3 The difference from Example 1 is that the nonwoven fabric obtained is as follows: The 80 mesh wire mesh is a plain weave wire mesh, the outer diameter of each of the vertical and horizontal wires constituting the mesh is 0.14 mm, the vertical and horizontal pitches are 0.32 mm, and the formed through holes have a diameter of about 0.3 mm in the MD direction and about 0.2 mm in the CD direction. Comparative Example 2

[0053] In Comparative Example 2, 30% by mass of the eccentric core-sheath type composite fiber and 70% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, a wire mesh having a mesh size of 80 mesh was used as a support in the hydroentanglement step, and the basis weight was 41.9 g / m 2 , thickness 0.88mm, density 0.048g / cm 3 The difference from Example 1 is that the nonwoven fabric obtained is as follows: The 80 mesh wire mesh is a plain weave wire mesh, the outer diameter of each of the vertical and horizontal wires constituting the mesh is 0.14 mm, the vertical and horizontal pitches are 0.32 mm, and the formed through holes have a diameter of about 0.3 mm in the MD direction and about 0.2 mm in the CD direction. Comparative Example 3

[0054] In Comparative Example 3, 80% by mass of the eccentric core-sheath type composite fiber and 20% by mass of rayon were used as the regenerated cellulose fiber to obtain the second raw fiber for forming the second web, and the basis weight was 42.4 g / m 2 , thickness 1.05mm, density 0.040g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. Comparative Example 4

[0055] In Comparative Example 4, the second web was not formed in the web forming process, and the lamination process was omitted. The eccentric core-sheath type composite fiber was used at 80 mass %, and the rayon was used at 20 mass %, and these were uniformly mixed to form the first raw fiber. The first raw fiber was then aligned in the fiber direction by a carding machine to form a fiber mass of 40 g / m. 2 The first web was formed to have a basis weight of 41.7 g / m 2 , thickness 0.98mm, density 0.043g / cm 3 This is different from Example 1 in that a nonwoven fabric having the above formula was obtained. (evaluation)

[0056] In Table 1, the differences in the liquid absorption time and liquid return amount between Examples 1 to 7 and Comparative Examples 1 to 4 mainly depend on the mesh size, the fiber type and its blend ratio of the first web, and the fiber type and its blend ratio of the second web.

[0057] In addition, Examples 1 to 7 and Comparative Examples 1 to 4 were manufactured using a common manufacturing apparatus, and the variations in their basis weight, thickness, and density are small and considered to be within the range of manufacturing error, so they are ignored. (Effect of mesh size)

[0058] Example 4 and Comparative Example 1 differ only in the mesh size among the fiber types and their blending ratios of the first web, the fiber types and their blending ratios of the second web, and the mesh size, and Example 6 and Comparative Example 2 differ only in the mesh size. Furthermore, Example 4 is significantly improved in the first liquid absorption time compared to Example 4 and Comparative Example 1. Furthermore, Example 6 is significantly improved in the first liquid absorption time compared to Comparative Example 2. This is thought to be due to the effect that the smaller mesh size increases the diameter of the through holes and the area of ​​the through holes, which makes it easier for the liquid on the surface side of the nonwoven fabric to come into contact with the hydrophilic rayon fibers of the second web through the through holes. (Effect of Fiber Type and Blend Ratio of First Web)

[0059] Examples 1 to 7 and Comparative Example 4 are different in that, in Examples 1 to 7, a laminate sheet is formed by laminating a first web and a second web, each of which has an eccentric sheath-core composite fiber content of 100% by mass, and hydroentangling them, whereas in Comparative Example 4, a second web is not used, and only a first web, each of which has an eccentric sheath-core composite fiber content of 80% by mass and a rayon fiber content of 20% by mass, is hydroentangled. The amount of liquid wetback in Comparative Example 4 tends to be greater than the amounts of liquid wetback in Examples 1 to 7. This is believed to be due to the fact that hydrophilic rayon fibers are distributed more on the skin side surface of Comparative Example 4 than on the skin side surface of Examples 1 to 7. (Effect of the fibers of the second web and their blend ratio)

[0060] Examples 1 to 7 and Comparative Example 3 each have the same configuration of the first web, but Examples 1 to 7 and Comparative Example 3 differ in the content of eccentric core-sheath type composite fibers and the content of rayon in the second web.

[0061] Fig. 3 is a graph showing the relationship between the content of rayon fiber contained in the second web and the liquid absorption time and the amount of liquid return, which was created based on the data in Table 1 for Examples 1 to 7 and Comparative Example 3. In Fig. 3, the liquid absorption time and the amount of liquid return when the content of rayon fiber is 20% by mass are those for Comparative Example 3, and the liquid absorption time and the amount of liquid return when the content of rayon fiber is 25%, 30%, 40%, 50%, 60%, 70%, and 100% are those for Examples 1, 2, 3, 4, 5, 6, and 7. It is observed that the liquid absorption time is the longest in the first absorption and decreases with the number of absorptions, while the amount of liquid return is the smallest in the first absorption and increases with the number of absorptions. This is presumably due to the fact that the rayon fiber contained in Examples 1 to 7 and Comparative Example 3 has a property of easily allowing the liquid to pass through once it has absorbed the liquid.

[0062] Also, when the rayon fiber content is low, the liquid absorption time is long, and when the rayon fiber content is low, the amount of liquid wet-back tends to be small. On the other hand, when the rayon fiber content is high, the liquid absorption time is short, and the amount of liquid wet-back tends to increase. The amount of liquid wet-back for the first time is kept small, and does not change significantly even when the rayon fiber content is changed.

[0063] The first absorption time of Comparative Example 3 (rayon fiber content 20%) is significantly longer than that of Example 1 (rayon fiber content 25%), reaching an uncomfortable level. Also, in Example 7 (rayon fiber content 100%), the amount of liquid wet-back the second time is significantly greater than that of Example 6 (rayon fiber content 70%), and in order to obtain an absorbent article that feels dry even immediately after the second absorption, it is safer to avoid using Example 7 and use, for example, Example 1.

[0064] In order to achieve a balanced improvement in the ability of the nonwoven fabric for absorbent articles to quickly transfer and absorb liquid administered to the skin-facing surface of the absorbent body, and the ability to prevent the liquid absorbed by the absorbent body from returning to the skin-facing surface, the rayon fiber content in the second web should be within the range of 25% by mass to 80% by mass.

Claims

1. A nonwoven fabric comprising composite fibers containing a polyolefin resin and regenerated cellulose fibers, The first web containing 90% by mass or more of the composite fiber and the second web containing 25% by mass or more of the regenerated cellulose fiber are overlapped and hydroentangled to form the web. The nonwoven fabric for absorbent articles has a large number of through holes passing through the nonwoven fabric in the thickness direction.

2. The nonwoven fabric for absorbent articles according to claim 1, The second web is a nonwoven fabric for absorbent articles containing 25 to 80% by mass of regenerated cellulose fibers and 20 to 75% by mass of the composite fibers.

3. The nonwoven fabric for absorbent articles according to claim 1 or 2, The nonwoven fabric for absorbent articles is a composite fiber that is an eccentric core-sheath type composite fiber in which the sheath portion is made of a polyethylene resin.

4. The nonwoven fabric for absorbent articles according to claim 3, The nonwoven fabric for absorbent articles is such that the sheaths of the eccentric core-sheath type composite fibers are not fused to each other, the sheaths are not fused to the regenerated cellulose fibers, and the regenerated cellulose fibers are not fused to each other.

5. The nonwoven fabric for absorbent articles according to claim 1, The composite fibers and the regenerated cellulose fibers are each short fibers, and at least the composite fibers in the first web and the regenerated cellulose fibers in the second web are entangled with each other.

6. a web forming process in which raw cotton of composite fiber containing polyolefin resin is loosened to form a first raw fiber, or raw cotton of the composite fiber and raw cotton of regenerated cellulose are loosened separately, and the loosened composite fiber and the regenerated cellulose fiber are mixed so that the composite fiber accounts for 90% by mass or more to form a first raw fiber, and the first raw fiber is carded to form a first web, and raw cotton of the regenerated cellulose fiber and raw cotton of composite fiber containing polyolefin resin are loosened separately, and the loosened regenerated cellulose fiber and the composite fiber are mixed so that the regenerated cellulose fiber accounts for 25% by mass or more to form a second raw fiber, and the second raw fiber is carded to form a second web; a lamination step of overlapping the first web and the second web to obtain a laminated web; a hydroentanglement step in which the laminate web is supported by a mesh-like support disposed on the second web side of the laminate web and travels together with the support, while high-pressure water is sprayed onto the laminate web from a number of spray nozzles disposed on the first web side, thereby hydroentanglement of the first raw fiber and the second raw fiber and obtaining a wet nonwoven fabric having a number of through holes; and a drying step of heating and drying the wet nonwoven fabric obtained in the hydroentanglement step.

Citation Information

Patent Citations

  • Nonwoven fabric containing cotton and its manufacturing method

    JP2016529412A